Basic Concept of Students' Morals Development Management from the Qur’an Perspective - Almafahir, Ahmad; Laila Fathiyyah; Maryam Arrosikha; Musthofa (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2024)
Moral degradation and character crises are worrying phenomena among students today. This research examines the basic concept of management of students’ moral development from the Qur’an perspective to overcome these problems. The research uses qualitative research with a library approach and uses thematic interpretation (maudu’i) and content analysis methods. This research explores verses from the Qur’an related to management and morals. The research results formulate the main principles in moral development management, including comprehensive planning, continuous implementation, comprehensive supervision, unity of command, decision-making based on wisdom, making the Prophet’s morals an example, and instilling the values ​​of justice and preventing evil. It is hoped that implementing these principles can help students develop noble morals, following the values ​​of the Qur’an as a guide to life for Muslims.